1990
DOI: 10.1163/156856190x00568
|View full text |Cite
|
Sign up to set email alerts
|

Acid-base interfaces in fiber-reinforced polymer composites

Abstract: The role of Lewis acid-base interactions at the fiber-matrix interface in composites is studied with both glass and Teflon fibers. In the glass fiber case, surface chemistry is modified with amino-, methacryloxy-and glycidoxy-silane coupling agents (A-1100, A-174 and A-187, respectively). Silane adsorption mechanisms as well as the properties of filament-wound, unidirectional epoxy and polyester composites are explained by a combination of X-ray photoelectron spectroscopy (XPS), scanning electron microscopy (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…It has long been known that treating the surface of a silica filler (colloidal, particulate, or fibrous) with a coupling agent improves the physical and chemical properties of a polymer matrix filled with such materials (1)(2)(3)(4). The match between polymer matrix and silane organofunctional group type and length has a bearing on the mechanical properties of the product (5).…”
Section: Introductionmentioning
confidence: 99%
“…It has long been known that treating the surface of a silica filler (colloidal, particulate, or fibrous) with a coupling agent improves the physical and chemical properties of a polymer matrix filled with such materials (1)(2)(3)(4). The match between polymer matrix and silane organofunctional group type and length has a bearing on the mechanical properties of the product (5).…”
Section: Introductionmentioning
confidence: 99%
“…1) from aqueous solution, displayed the typical smooth surface morphology (Fig. E-glass fibers (1 gm; Ahlstrom Glassfibre Ltd.; 11 mm thickness; BET surface area, 0.7 cm 3 /g; density, 2.50 g/cm 3 ; sized with pure water then 2a) seen previously (24)(25)(26). Identical treatment of the glass fibers with the isocyanurate silane, but from CCl 4 solution, resulted in unprecedented air dried and cut into 8 mm lengths) were magnetically stirred in a solution of the isocyanurate silane ( Fig.…”
Section: Methodsmentioning
confidence: 59%
“…2b), with the isocyanurate silane clustering or aggregating into hydrophobic domains. Such domain formation fibers were washed with CCl 4 (3 1 100 ml) and then oven dried at 120ЊC was once previously observed (24). The surprising SEM pictures revealed environments cannot remove all the surface water from glass.…”
Section: Methodsmentioning
confidence: 66%
“…Previous SEM pictures of silane-coated glass fibers have revealed a smooth surface morphology (36,37). Treatment of glass fibers with isocyanurate silane from ethanol and toluene, respectively, revealed that the silane formed bridges between nearby fibers (Figs.…”
Section: Sem Analysismentioning
confidence: 93%